2013
DOI: 10.13172/2052-0077-2-11-812
|View full text |Cite
|
Sign up to set email alerts
|

Localised extranodal non-Hodgkin's lymphoma of the tonsil: report of a rare case

Abstract: Introduction Non-Hodgkin's lymphoma of the Waldeyer's ring is a relatively rare entity and the palatine tonsil is the most frequently involved site. Although, the exact aetiology remains unclear, a number of predisposing factors have been identified, including human immunodeficiency virus and Epstein-Barr infection. We report a case of localised extranodal non-Hodgkin's lymphoma of the tonsil. Case report A 64-year-old woman presented with a sore throat. On physical examination, an approximately 2 × 1 cm smoot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…Next common location is orbital ENL (21%) and our observation is in concordance with Mishra P et al [2] Peak incidence in tonsils is seen in 6-7 decade with male preponderance. [7,12] In our study, tonsillar ENL is more in 4 th and 5 th decade with male: female ratio being 1.8:1. High index of suspicion needed as tonsillar ENL presents as progressive sore throat, partially relieved on treatment.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Next common location is orbital ENL (21%) and our observation is in concordance with Mishra P et al [2] Peak incidence in tonsils is seen in 6-7 decade with male preponderance. [7,12] In our study, tonsillar ENL is more in 4 th and 5 th decade with male: female ratio being 1.8:1. High index of suspicion needed as tonsillar ENL presents as progressive sore throat, partially relieved on treatment.…”
Section: Discussionsupporting
confidence: 49%
“…Most of tonsillar lymphoma are B cell phenotype with 67-96 % exhibiting DLBCL histology and DLBCL is often aggressive. [7,12] High grade transformation of pre-existent low-grade mucosa associated lymphoid tissue lymphoma (MALToma) or follicular lymphoma into DLBCL is known to occur. [1] In the present study, all tonsillar lymphoma were of B cell subtype with diffuse large cell lymphoma in 80 % cases (Fig 1).…”
Section: Discussionmentioning
confidence: 99%
“…
he tonsil is a rare site of lymphoma. On this accordance, single cases have been reported from China, [1] Greece, [2] India, [3,4] Japan, [5] and Turkey. [6] Therefore, this paper presents five cases found in Nigeria among the Ibo indigenous group.
…”
mentioning
confidence: 88%
“…Squamous cell carcinoma (SCC) is the most common malignancy followed by Non-Hodgkin's lymphomas (NHL) in the tonsil. NHL of the oral cavity and oropharynx usually account for 13% of all primary extra nodal NHL with approximately 70% occurring in the tonsils [26]. The palatine tonsil is the most frequently involved site followed by palate, gingiva and tongue.…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 99%
“…The peak incidence is in sixth and seventh decades of life with slight male predominance. Clinical presentation is not specific and is due to of asymmetrical tonsillar enlargement [26]. Babu et al [24] reported a total of 5 cases of tonsillar malignancy-two undifferentiated carcinomas, two NHLs, and one SCC.…”
Section: International Journal Of Medical Research and Reviewmentioning
confidence: 99%